Strategic Responses to Pressures in the Indonesian Banking Sector: A Comparative Study of BCA and BRI - Sumini Salem; Kevin Ray (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2026)
Indonesian banks faced shifting funding conditions, credit risk, digital competition, and increased regulatory demands between 2023 and 2025. The study examines sector pressures and evaluates the responses of PT Bank Central Asia Tbk (BCA) and PT Bank Rakyat Indonesia (Persero) Tbk through various funding, lending, risk-management and digital strategies. A descriptive comparative case study design was employed, drawing on audited financial statements, annual reports, regulatory publications, and other credible secondary sources. Financial ratios were selected and then combined with PESTEL and SWOT analyses to interpret the external environment, strategic responses and financial outcomes of both banks. The results show that BCA followed a more stability-oriented approach supported by a higher CASA ratio, a lower Loan-to-Deposit Ratio, better asset quality and more stable profitability. BRI adopted a more expansionary strategy emphasizing MSME lending and financial inclusion. This approach supported greater lending activity and rising earnings per share, but it also resulted in higher liquidity pressure, higher credit exposure, weaker profitability margins, and a higher dividend payout ratio. The study concludes that banks operating in the same sector conditions could generate different financial results due to their strategic priorities. Effective responses to banking-sector pressure require a balance among growth, funding capacity, credit quality, profitability, and long-term financial flexibility.